Integrated Static Reservoir Modeling of Yan’an Formation, X-area, Ordos Basin, China - Loo , Sheau Huey (Universiti Teknologi PETRONAS, 2016)
The construction of a static reservoir model often requires integration of dataset from multidiscipline studies. However, for onshore X-area of Ordos Basin, only partial ready dataset is available for modeling activities. Thus, it is very crucial that sufficient dataset is generated and derived based on the limited data source. This main focus of this study will be divided into three (3) parts which are geophysical, petrophysical and geomodeling studies with aim to generate adequate data inputs for static model construction of X-area.